(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Changes in the security environment and opportunities in the modern world present increasing challenges for the armed forces of democratic states to staff their structures. The article examines the issues related to the motivation for choosing the military career of an officer. Based on a survey conducted with cadet candidates and a comparative analysis with previous research, the main variables influencing the choice of the officer profession and joining the armed forces are derived. The obtained results could contribute to the improvement of the current system for motivating military personnel and increase the image of the military profession.